LEGAL PROTECTION OF OWNERSHIP OF PROPERTY RIGHTS CERTIFICATES IN FORESTRY CULTIVATION AREAS - Riswandi; Rosmini; Nur, Insan Tajali (Awang Long Law Review, 2024)
The background of this study examines the overlapping authority in determining forest areas and its implications for the legal protection of ownership of Land Ownership Certificates (SHM). This study found that overlapping authority occurred due to the absence of confirmation of forest area boundaries and systematic spatial planning, thus triggering conflict between communities that own SHM and forestry policies. The state has an obligation to protect community rights, including land rights as evidenced by SHM. The purpose of the study is to answer two things, first, to find out clarity about the factors that cause overlapping in determining forest areas in the Forestry Law, by analyzing the problems that arise from existing provisions. Second, the study looks at the form of legal protection provided by the state to the community in dealing with the problem of overlapping determination of forest areas in Kutai Kartanegara Regency. The type of this research is sociological legal research or Sociolegal studies. The research was conducted in the East Kalimantan Province, (East Kalimantan Province Environmental and Forestry Service, and the East Kalimantan Province Agrarian Spatial Planning Office/National Land Agency). The focus of this research was conducted in Sepati Village, Anggana District, Kutai Kartanegara Regency. This research will use selected respondents (purposive sampling) within the Kutai Kartanegara Regency in the area around the forestry cultivation area, namely Village Heads and Community Leaders. Specifically for respondents, researchers will conduct an interview process (deep-interview) including the use of snow-ball techniques with respondents who have a structured information network. The results of this study conclude that resolving overlapping authorities requires a comprehensive approach involving all related parties. The steps taken are comprehensive spatial planning, land dispute resolution, confirmation of forest area boundaries, strict law enforcement, strengthening institutions and non-litigation resolution.